Metode Peningkatan Aktivitas Perawatan Gigi dan Mulut Pada Anak Berkebutuhan Khusus - Suharjono Suharjono (Journal of Oral Health Care, 2018)
This booklet is a small book (half quarto) and thin, no more than 30 pieces of back and forth that contains about writing and drawing. The term booklet comes from books and leaflets meaning that booklet media is combination of leaflets and books with small formats (sizes) such as leaflets, it’s just how presentation is much shorter than the book. Children with mental disabilities are individuals who experience obstacles or delays in mental development far below the average so that it has difficulty to learn, communicate, and socialize as well as self care, especially brushing teeth. Booklet that contains how to care for teeth, especially how to brush your teeth can be a guidline for treating teeth in children with mental disabilities in SLB and availability is still very minimal even can be said none at all so that a teacher is still very wide open and still allow the media booklet to be developed. Availability of booklets in SLB Class 1 Yogyakarta City as a media as well as guide for mentally handicapped children to guide tooth care by brushing teeth. Research methods to achieve to goal of Quasi Experiments with fishbone diagram design. Pre-Post Test with control design. The population in this study are mentally disabled children in SLB Class 1 Yogyakarta City. Results from the examination were recorded in the OHIS format, than collected and analyzed using a T-Test statistic test. Using parametric statistic test Paired Sample T-Test there is a significant difference of OHIS score after using booklet p value < 0,05 so it can be stated that booklet can influence in dental and mouth care (OHIS score) children with mental disabilities SLB Class 1 Yogyakarta City